The Relationship between Government Spending and Economic Growth Revisited - Wahyudi, Wahyudi (International Journal of Economics and Financial Issues, 2020)
This study aims to analyze and verify the relationship between government spending and economic growth. This relationship has been a hot topic for debate among economists, with plenty of research done and being done upon it. This particular study uses panel data from 34 provinces in Indonesia during the 2014-2018 period. During this time, Indonesia’s government allocated significant amount of its annual budget towards infrastructure. The estimated econometric test result using the Granger Causality Test did not find support for the effect of economic growth on government spending. Conversely, government spending has a significant effect on economic growth. This study provides support for Keynesian economic system, where government spending is used as a policy instrument to encourage economic growth in a nation. Keywords: Government Spending, Economic Growth, Keynes, Wagner JEL Classifications: B22, Q01, Q12 DOI: https://doi.org/10.32479/ijefi.10614